Risky sexual behavior and substance use among adolescents: A meta-analysis. (May 2015) - Ritchwood, Tiarney D.; Ford, Haley; DeCoster, Jamie; Sutton, Marnie; Lochman, John E.
Abstract: This study presents the results of a meta-analysis of the association between substance use and risky sexual behavior among adolescents. 87 studies fit the inclusion criteria, containing a total of 104 independent effect sizes that incorporated more than 120, 000 participants. The overall effect size for the relationship between substance use and risky sexual behavior was in the small to moderate range ( r  = .22, CI = .18, .26). Further analyses indicated that the effect sizes did not substantially vary across the type of substance use, but did substantially vary across the type of risky sexual behavior being assessed. Specifically, mean effect sizes were the smallest for studies examining unprotected sex ( r  = .15, CI = .10, .20), followed by studies examining number of sexual partners ( r  = .25, CI = .21, .30), those examining composite measures of risky sexual behavior ( r  = .38, CI = .27, .48), and those examining sex with an intravenous drug user ( r  = .53, CI = .45, .60). Furthermore, our results revealed that the relationship between drug use and risky sexual behavior is moderated by several variables, including sex, ethnicity, sexuality, age, sample type, and level of measurement. Implications and future directions are discussed. Highlights: Substance use is more strongly related to risky sex among females than males. Ethnicity moderated the relationship between substance use and risky sex. Type of drug had little impact on the link between substance use and risky sex. Event-level studies did not moderate the link between substance use and risky sex.